2017
DOI: 10.1111/jdv.14085
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the role of imiquimod in lentigo maligna and lentigo maligna melanoma: need for standardization of treatment schedule and outcome measures

Abstract: Lentigo maligna (LM) is an in situ variant of melanoma. Our objective was to systematically review clinical and histological clearance and recurrence rates of imiquimod treatment of LM with emphasis on progression to lentigo maligna melanoma (LMM). PubMed, EMBASE and the Cochrane library were searched from inception to May 2015. Articles were included if they described histologically proven LM treated with imiquimod 5% monotherapy or combined with another topical therapy. Analysed outcomes were clinical and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
80
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 59 publications
3
80
2
3
Order By: Relevance
“…Previous retrospective studies have documented a clinical response rate of 73% after a 40-month follow-up (Fosko et al, 2018), while a systematic review of mainly retrospective studies showed a 77% histological clearance rate (Tio et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous retrospective studies have documented a clinical response rate of 73% after a 40-month follow-up (Fosko et al, 2018), while a systematic review of mainly retrospective studies showed a 77% histological clearance rate (Tio et al, 2017).…”
mentioning
confidence: 99%
“…Specifically, the better response to imiquimod 5% was present in patients that developed an intense cutaneous reaction with an intense inflammation (Tio et al, 2017). This is due to the mechanism of action of the drug, that is, a Toll-like receptors seven and eight agonist, which allows the release of Interferon-alfa, Tumor Necrosis Factor-alfa and Interleukin-6, increasing the local and systemic immune response.…”
mentioning
confidence: 99%
“…Topical imiquimod is an off‐label option for the treatment of patients with LM who do not qualify for or do not opt for surgical treatment. Imiquimod is applied for a prolonged period of time to achieve a sufficient inflammatory response . We hypothesize that lymphoedema may complicate treatment of patients with LM using topical imiquimod.…”
mentioning
confidence: 99%
“…2,3 Complete clinical response rates for LM treated with imiquimod vary from 37Á1% to 100%. [4][5][6] We report three patients with LM who developed lymphoedema following application of topical imiquimod.…”
mentioning
confidence: 99%
See 1 more Smart Citation